How the natural environment affects psychological recovery: A case study in Changsha, China. - Kexin Zhao; Shuangquan Zhang; Fengying Zhao (PLoS ONE)
Previous research has demonstrated the role of urban forest parks in the recovery of human psychological well-being, but there is a lack of explanation of the "how" and "why" of experiences in urban forest parks that promote psychological recovery. This study used the structural equation model (SEM) method to explore the influence mechanism and path of the natural environment on the public's psychological recovery evaluation in urban forest parks through 485 questionnaires. The study findings reveal the following: (1) In urban forest parks, natural environment perception (NEP) exerts significant positive effects on leisure involvement (LI), place attachment (PA), and restorative environment perception (REP). While NEP does not directly influence psychological recovery evaluation (PRE), its effects are mediated through four distinct pathways: First, via the complete mediation of REP; Second, through the serial mediation of LI and REP; Third, by the chain mediation of PA and REP; Fourth, through the sequential chain mediation of LI, PA, and REP. (2) Leisure involvement significantly enhances both place attachment and restorative environment perception. Additionally, place attachment exhibits a significant positive effect on restorative environment perception, while restorative environment perception demonstrates a robust positive association with psychological recovery evaluation. (3) Demographic variables, including gender, age, and educational level, did not demonstrate significant moderating effects on the structural relationship between natural environment perception and psychological recovery evaluation. The findings may have the potential to offer fresh ideas for enhancing the recovery effect of urban forest parks and have significant implications for their management and sustainable development.